TINGKAT DAN KONDISI DAYA SAING KOMODITAS UNGGULAN PERIKANAN TANGKAP KOTA KENDARI - Fajriah Fajriah (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2016)
The research objective are to analyze the conditions of competitiveness and the relationship between the components of the leading commodity determinant of the competitiveness of fisheries Kendari. The information generated from this study are expected to be a reference for the government of Kendari in making strategic policy in planning the development of the fisheries sector by leading commodity. This recent research conducted in the City of Kendari, Southeast Sulawesi Province in May to August 2015. This study used a descriptive analysis with diamond theory approach porter. The analytical method used in the theory of diamond porter circumstances include component factors of production, the state of demand for goods and services, state suppliers and other industry and corporate strategy, structure and state of an industry competition area. The results obtained in this study based on the competitive advantages that leading commodity of fisheries in Kendari been competitive and based analisis linkages between the main components that most of the linkages between the main components support each other, unless that component related industries and supporting the market structure, competition and corporate strategy have linkage relationships that do not support each other, so we need the right policies from the government.Keywords: Competitiveness, Commodities, Capture Fishery